PENATAAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA SEBAGAI USAHA KECIL SELARAS DENGAN TATA RUANG WILAYAH KOTA PEKALONGAN - Esmara Sugeng; Listyo Budi Santoso (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Vendors  included  in  the  category  of  small  businesses,  and  also  as  an  integral  part  of business  which  is  the  economic  activity  of  society.  Vendors  have  the  position,  potential and  strategic  role  to  realize  the  structure  of  the  national  economy  that  increasingly balanced by economic democracy Relative to the street hawkers as a small business need to  be  more  empowered  to  take  advantage  of  business  opportunities  and  address challenges  of  economic  development  in the future.  Arrangement  of street  vendors is  not an  easy task, because it involves the  lives  of  many that can be said to reflect the  life  of "grassroots", so that the handling of policy and strategy requires a comprehensive and full of wisdom and humanity.Key word : small business, Empowerment, spatial